Plasmids Carrying blaCMY -2/4 in Escherichia coli from Poultry, Poultry Meat, and Humans Belong to a Novel IncK Subgroup Designated IncK2 - Seiffert, Salome N.; Carattoli, Alessandra; Schwendener, Sybille; Collaud, Alexandra; Endimiani, Andrea; Perreten, Vincent (Frontiers in Microbiology, 2017)
The blaCMY-2/4-carrying IncB/O/K-like plasmids of seven Escherichia coli strains from poultry, poultry meat and human urine samples were examined using comparative analysis of whole plasmid sequences. The incompatibility group was determined by analysis of the incRNAI region and conjugation assays with strains containing the IncK and IncB/O reference plasmids. Strains were additionally characterized using MLST and MIC determination. The complete DNA sequences of all plasmids showed an average nucleotide identity of 91.3%. Plasmids were detected in E. coli sequence type (ST) 131, ST38, ST420, ST1431, ST1564 and belonged to a new plasmid variant (IncK2) within the IncK and IncB/O groups. Notably, one E. coli from poultry meat and one from human contained the same plasmid. The presence of a common recently recognized IncK2 plasmid in diverse E. coli from human urine isolates and poultry meat production suggests that the IncK2 plasmids originated from a common progenitor and have the capability to spread to genetically diverse E. coli in different reservoirs. This discovery is alarming and stresses the need of rapidly introducing strict hygiene measures throughout the food chain, limiting the spread of such plasmids in the human settings.